Maternal health literacy and prevention of acute respiratory infection in toddlers - Dwi Yulia Maritasari; Febria Listina; Adila Tri Ayu; Anandha Widya Putri Rahmadhina; Aniza Salzadela Pradita; Difa Masya Gantha; Dinda Mutiara Azmi; Intan Nabela Septiyana; Muhammad Zaidan Amrullah; Niken Junia Sabila; Putri Sari Ramadhani; Solvia Atika Maulana (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Acute Respiratory Infection (ARI) is one of the leading causes of infant mortality worldwide, especially in developing countries. Lack of health literacy among mothers of toddlers is one factor that worsens the early treatment of ARI. Purpose: To determine the effectiveness of leaflet-based communicative counseling in improving the health literacy of mothers of toddlers to prevent ARI. Method: The research design was a quantitative pre-experimental study with a one-group pretest-posttest design. The sample in this study was all mothers of 31 toddlers detected with ARI, selected using a total sampling technique. The research instrument was a valid and reliable questionnaire used to measure maternal knowledge before and after the intervention. Result: The results showed a significant increase in maternal knowledge after counseling (p = 0.000). Conclusion: This indicates that leaflet-based communicative counseling is efficacious in improving the health literacy of mothers of toddlers. It is recommended that health workers at community health centers routinely provide similar counseling.